The impact of economic sanctions on cancer diagnosis and treatment in Iran: a qualitative study - Leila Haghjou; Leila Mounesan; Aziz Shamsi; Maryam Nazari; Najmeh Bahmanziari; Mohammad Shirkhoda; Saeid Amanpour; Alireza Abdollahi; Kazem Zendehdel; Hamideh Rashidian (BMC, 2024)
Abstract Background The economic sanctions imposed on Iran have had a significant impact on the country's healthcare system. The sanctions have affected the availability and affordability of cancer diagnosis and treatment services, leading to a range of challenges for patients with cancer. This study aimed to explore these challenges and gain a deeper understanding of the impact of economic sanctions on cancer care in Iran. Methods The research method involved qualitative in-depth interviews with 53 experts, including clinical and basic sciences specialists, who were selected through purposeful sampling. The data were analyzed through qualitative content analysis using MAXQDA 2020. Results A total of 900 codes were identified, categorized into three primary groups-input, process, and output-and further divided into 13 subcategories. Within the input category related to health systems providing cancer care to patients, several critical issues emerged. These included instability in financing mechanisms and regulations, shortages of materials, low-quality imported materials, high material prices, and loss of human resources. Meanwhile, in the process of delivering diagnostic and treatment procedures to cancer patients, concerns centered around delayed and inadequate care, non-adherence to guidelines, limited international collaborations, and reduced provider satisfaction. Finally, during the output phase, the main subcategories extracted were lower effectiveness, increased adverse events, and increased equity gaps. Conclusions Although economic sanctions against Iran have not officially targeted healthcare and access to drugs, they have restricted access to standard equipment and modern technologies, leading to increased delays, misdiagnosis, and diagnostic and therapeutic side effects in cancer patients to the point of death.